PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA DEWANGGA WEDDING JAKARTA TIMUR - Irma Sayyidina; Sugeng Santoso (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to find out whether there is an influence between Instagram social media marketing and service quality on the decision to use dewangga wedding services in East Jakarta. This study uses a quantitative scale with a Likert scale (scale 1 to 5). Where each variable uses a list of questionnaire questions, the population in this study is all consumers of wedding dewangga and uses a sample of correlational descriptive methods with a minimum of 30 subjects. Data processing uses SPSS version 26 with descriptive analysis and testing of multiple liner hypothesis. The results of the study showed that: The Instagram social media marketing variable has a positive and significant effect on the decision to use it alone, The variable of service quality has a positive and significant effect on the service decision. The variables of social media marketing, Instagram, and service quality affect the decision to use services simultaneously and together on the decision to use services.